An Assessment of Women Education in India - Amit Anand (PT FORMOSA CENDEKIA GLOBAL, 2022)
Women Education refers to any form of Education that aims at improvement of knowledge, Skill Intellectual and Physical Competence of Female Child and growing Women. It includes school, college and university level education, Vocational, Technical, Professional as well as Health Education. Indian Constitution guarantees equal rights and opportunities to both men and women alike. All round development of any Nation depends more on women folk of the society. During British and Mogul Rule in India people kept their female children mostly to household work and family duties. They did not get opportunities like ancient women belonging to the earliest Period of History. Even now we remember ladies like Sita, Savitree, Aamrpali, Gargi, Maîteryei, Bharti, wife of Mathili Scholar, Mundan Mishra. Laxmi Bai, Savitri Rao Phule, Jyotiba Phule to name a few. They ardently advocated for the upligender of women in Society. In their Age, they raised their voices against the Patriarchial Dominance and gender – discrimination. Rather, women folk was upressed, tortured physically assaulted by high - ups, British officers, Nawabs and Zamindars. Henc no proper schooling was provided to female child. Before Common men the burning problem was to get their female children married at the earlier stage of Life. This was the usual practice to avoid any sexual assault on women and hence education was provided only to male - children because they are supposed to be bread- winner for their families.The system of ‘Satti – Pratha” and Child- marriage” was in practice to provide safety to women. To promote male- child Education was the only option left to middle - Class family and poor people of the society, Before 1947, only a few fortunate Family could provide Educational Facilities to their daughters .They got full opportunities to study at university Level and even to visit foreign Countries for higher education